2013
DOI: 10.1177/1708538113487335
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of temporal artery pseudoaneurysms

Abstract: Limited evidence of minimal invasive treatment for superficial temporal artery pseudoaneurysm is available. Based on this review combined with our limited experience, we suggest thrombin injections to be considered as the future primary treatment modality. In the case of unsuccessful exclusion of the aneurysm, surgical excision can be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Other options such as US thrombin injection and endovascular embolisation are currently infrequently used 7. Endovascular treatment options carry risks that do not apply to open surgery, such as non-target/distal embolisation and the complications of arterial puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Other options such as US thrombin injection and endovascular embolisation are currently infrequently used 7. Endovascular treatment options carry risks that do not apply to open surgery, such as non-target/distal embolisation and the complications of arterial puncture.…”
Section: Discussionmentioning
confidence: 99%
“…STA aneurysms as a result of trauma represent <1% of reported aneurysms,8 and the authors found only one other idiopathic case described in the English literature, which was speculatively attributed to repeated Valsalva manoeuvres by the patient 7. Although the diagnosis of STA pseudoaneursym can be made clinically,6 FNA is a useful diagnostic investigation. In our case, the blood-stained aspirate was helpful in suggesting the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular lesions, such as vascular tumour, arteriovenous malformation or a meningeal aneurysm, are rarely considered in the age group of this patient. Imaging modalities that can be used to confirm or exclude the differential vascular diagnoses of a probable STA aneurysm include sonography, CT, MR and digital subtraction angiography (DSA) 6. CT and MR have the advantage of being non-invasive imaging techniques that can easily delineate adjacent soft tissue structures.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…First attempts at the treatment of pseudoaneurysms of the external carotid artery were performed by Hunter in the 18th century who showed the value of proximal artery ligation [10]. Treatment options for traumatic pseudoaneurysms include simple resection of the aneurysm, coil embolization [11] and direct thrombin injection [12], proximal ligation of parent artery or trapping of the aneurysm [13]. However, an open approach to many of these lesions may be fraught with peril due to grossly distorted and oedematous tissue planes that often have heavy bacterial colonisation [8].…”
Section: Case Reportmentioning
confidence: 99%